BIOSTIMULATORY EFFECT OF CATTLE DUNG ON LEAD DECONTAMINATION POTENTIAL OF INDIGENOUS FUNGAL POPULATION ISOLATED FROM SPENT ENGINE OIL-POLLUTED SOIL - Adeniyi Olarewaju Adeleye; Abubakar Ibrahim; Michael Edet Nkereuwem; Peter Gimba Shiaka; Mohammed Bello Yerima (Science Heritage Journal)
This study assessed the effect of cattle dung (CD) enhanced with fungi isolated from spent engine oil (SEO)-polluted soil on Lead (Pb) decontamination. Twenty plastic bottles containing 20 g of soil each were prepared with varying weights of CD and volumes of fungal isolates in potato dextrose broth each. The mixture was incubated at room temperature. It was a 4 x 2 factorial experiment. Atomic absorption spectrophotometer was employed to determine Pb decontamination of the bio-enhanced fungal consortium in the 2nd, 4th and 6th week of incubation. At the 2nd week, there was no significant (p> 0.05) difference between the addition of 10 g of CD (0.1750 mg/kg) and 15 g of CD (0.1750 mg/kg). At the 6th week, the lowest concentration (0.0400 mg/kg) of Pb was recorded with the addition of 20 g of CD and inoculation with fungal isolate (15 mL). Fungi bio-enhanced with CD influenced decontamination of Pb in SEO-contaminated soils in this study.